2010
DOI: 10.1002/chem.200902991
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the Equatorial Environment on Oxo‐Group Silylation of the Uranyl Dication: A Computational Study

Abstract: We thank the Insitut Universitaire de France, CALMIP, CCRT, and CINES for their grant of computing time; CNRS, UPS, and CEA for financial support of this work; and the EPSRC and the University of Edinburgh for funding. Supporting information:Supporting information for this article is available online at http://dx.doi.org/10.1002/chem.200902991 Cartesian coordinates of the optimised structures are included. Keywords:density functional calculations;equatorial ligands;macrocycles;silylation;uranium Synopsis:A DF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 40 publications
(30 reference statements)
1
31
0
Order By: Relevance
“…The average U-O OTf distance (av. U-O = 2.39 Å) is similar to other U(IV)-O OTf distances, [20][21][22] but is slightly longer than those observed in the structurally related complex, U IV (OTf) 4 (DME) 2 (av. U-O = 2.28 Å), 23 which is probably a result of the steric bulk of the dppmo ligands.…”
supporting
confidence: 67%
See 2 more Smart Citations
“…The average U-O OTf distance (av. U-O = 2.39 Å) is similar to other U(IV)-O OTf distances, [20][21][22] but is slightly longer than those observed in the structurally related complex, U IV (OTf) 4 (DME) 2 (av. U-O = 2.28 Å), 23 which is probably a result of the steric bulk of the dppmo ligands.…”
supporting
confidence: 67%
“…[2][3][4][5][6][7] For example, Arnold and co-workers demonstrated that sequential reaction of U VI O 2 (THF)(H 2 L) (L = polypyrrolic macrocycle) with KN(SiMe 3 ) 2 and FeI 2 resulted in formation of the U(V) silyloxide, [U V O(OSiMe 3 )(THF)Fe 2 I 2 L]. 7 Similarly, our research group has demonstrated that reaction of U VI O 2 ( Ar acnac) 2 ( Ar acnac = ArNC(Ph)CHC(Ph)O, Ar = 3,5-t Bu 2 C 6 H 3 ), 8 with a mixture of B(C 6 F 5 ) 3 and HSiR 3 (R = Ph, Et), 9,10 or with Ph 3 SiOTf alone, 11 results in formation of the reductive silylation products, U V (OSiR 3 )(OB{C 6 11 respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The low yields of 2 and lack of obvious reducing agent in the synthetic procedure led us to investigate reactions at lower temperatures ( Figure 5). It is clear from these investigations that two competing reactions occur, one at lower temperature that involves metallation of the uranyl oxo, and one at 44,45 While a detailed evaluation of the mechanism of formation of 2 is ongoing, the observations described above suggest that two competing, reductive pathways occur that involve either U-N or N-Si bond homolysis (for a speculative mechanism see Figure SI. 19).…”
Section: Mechanistic Insight Into the Formation Ofmentioning
confidence: 99%
“…[13][14][15][16][17][18][19] Reductive silylation was rst demonstrated by Arnold and co-workers, who showed that a strongly donating macrocyclic ligand promoted the reductive silylation of UO 2 (THF)(H 2 L) (L ¼ 'Pacman' polypyrrolic macrocycle) to produce the U(V) silyloxide, [UO(OSi-Me 3 )(THF)Fe 2 I 2 L]. 13,14,20,21 Subsequently, our research group reported the reductive silylation of the b-ketoiminate complex, UO 2 ( Ar acnac) 2 ( Ar acnac ¼ ArNC(Ph)CHC(Ph)O; Ar ¼ 3,5-t Bu 2 C 6 H 3 ) using a combination of B(C 6 F 5 ) 3 and HSiR 3 (R ¼ Ph, Et) to generate U(OSiPh 3 )(OB{C 6 F 5 } 3 )( Ar acnac) 2 22 and [U(OSiEt 3 ) 2 ( Ar acnac) 2 ][HB(C 6 F 5 ) 3 ]. 23 In our original report we argued that the strong electron donating ability of the b-ketoiminate ligand, Ar acnac, 22 activated the uranyl oxo groups toward functionalization.…”
Section: Introductionmentioning
confidence: 99%